2022
DOI: 10.1038/s43018-022-00353-6
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular tenascin C triggers sequential activation of macrophages and endothelial cells to generate a pro-metastatic vascular niche in the lungs

Abstract: Disseminated cancer cells frequently lodge near vasculature in secondary organs. However, our understanding of the cellular crosstalk invoked at perivascular sites is still rudimentary. Here, we identify intercellular machinery governing formation of a pro-metastatic vascular niche during breast cancer colonization in the lung. We show that specific secreted factors, induced in metastasis-associated endothelial cells (ECs), promote metastasis in mice by enhancing stem cell properties and the viability of cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 67 publications
1
38
0
Order By: Relevance
“…Perivascular CAFs secrete CXCL12, IL-33 and SDF-1α in response to cancer cell activation (63). High infiltration of macrophages in vascular sites can be responsible for pro-metastatic niche formation (78). In a BC model, perivascular macrophages were activated by the cancer cell-derived ECM protein tenascin (TNC) (78).…”
Section: Blood Vessel Ecsmentioning
confidence: 99%
“…Perivascular CAFs secrete CXCL12, IL-33 and SDF-1α in response to cancer cell activation (63). High infiltration of macrophages in vascular sites can be responsible for pro-metastatic niche formation (78). In a BC model, perivascular macrophages were activated by the cancer cell-derived ECM protein tenascin (TNC) (78).…”
Section: Blood Vessel Ecsmentioning
confidence: 99%
“…Recent literature suggests that tumor cells prepare the site for tumor cell homing (the so-called ‘pre-metastatic niche’) for future metastasis by employing several cell types, including fibroblasts, ECs, macrophages and likely others. Moreover, TNC plays an important role in this pre-metastatic niche ( Hongu et al, 2022 ). With regard to how this niche is prepared, lactic acid-associated low pH ( Riedel et al, 2022 ) (with no explicit link to TNC so far) and extracellular vesicles (EVs) secreted by the tumor have become a recent focus of interest ( Guo et al, 2019 ; Dong et al, 2021 ).…”
Section: Tenascin-c Promotes Plasticity Invasion and Metastasismentioning
confidence: 99%
“…Transcriptomic analysis of ECs from murine lung metastasis combined with loss- and gain-of-function studies has revealed that cancer-cell-derived TNC activates secretion of TNFα and nitric oxide in macrophages in a TLR4-dependent manner ( Hongu et al, 2022 ). This triggers gene expression in ECs that promoted metastasis where expression of four factors, INHBB (inhibin β B), laminin α1, osteoprotegerin (OPG) and secreto-globulin family 3A member 1), were found to be crucial and correlated with worsened survival of breast cancer patients ( Hongu et al, 2022 ) ( Fig. 2 D).…”
Section: Tenascin-c Promotes Plasticity Invasion and Metastasismentioning
confidence: 99%
“…It was previously established that the endothelium serves as a systemic amplifier of primary tumour-derived signals 23,24 . Here, clustering of lung ECs revealed the emergence of cycling ECs as well as a shift of general capillary ECs (gCap) 25,26 towards an activated phenotype as a response towards arriving TCs.…”
Section: Mainmentioning
confidence: 99%
“…As the lung endothelium harbours two distinct vascular beds that are defined by less penetrable gCaps and more permissive aerocytes (aCap) 23, 24 ( Fig. 3a ), we tested whether distinct vascular niche occupancy could drive the observed differential TC behaviour.…”
Section: Mainmentioning
confidence: 99%